How to Optimize Activated Partial Thromboplastin Time (APTT) Testing: Solutions to Establishing and Verifying Normal Reference Intervals and Assessing APTT Reagents for Sensitivity to Heparin, Lupus Anticoagulant, and Clotting Factors - Favaloro, Emmanuel J.; Kershaw, Geoffrey; Mohammed, Soma; Lippi, Giuseppe (Seminars in Thrombosis and Hemostasis, 2019)
The activated partial thromboplastin time (APTT) assay is a very common coagulation test, used for several reasons. The test is conventionally used for assessing the contact factor (intrinsic) pathway of blood coagulation, and thus for screening deficiencies in this pathway, most typically factors VIII, IX, and XI. The APTT is also sensitive to contact factor deficiencies, including factor XII, prekallikrein, and high-molecular-weight kininogen. The APTT may also be elevated in a variety of conditions, including liver disease, vitamin K deficiency, and disseminated intravascular coagulation. The APTT can also be used for monitoring unfractionated heparin (UFH) therapy, as well as for screening lupus anticoagulant (LA) or for assessing thrombosis risk. Which of these separate uses is important to a given laboratory or clinician depends on the laboratory and the clinical context. For example, UFH sensitivity is important in hospital-based laboratories, where UFH therapy is used, but not in hospital-based laboratories where low-molecular-weight heparin (LMWH) is largely employed or where UFH may be assessed by anti-factor Xa testing, or in private/community laboratories not associated with a hospital system. High sensitivity to (low levels of) factors VIII, IX, and XI is generally preferred, as their deficiencies are clinically significant. Also preferred, but not usually achieved, is low sensitivity to factor XII and other contact factors, as these deficiencies are usually asymptomatic. Nevertheless, a good knowledge of factor sensitivity is usually needed, if only to help explain the reasons for a prolonged APTT in a given patient, or whether factor testing or other investigation is required. A good working knowledge of reagents sensitivity to LA is also advisable, especially when the reagent is used as part of a LA test panel, or else as a “general-purpose screening reagent.” The current report is aimed at providing some guidance around these questions, and is intended as a kind of “how to” guide, that will enable laboratories to assess APTT reagents in regard to their sensitivity to heparin, LA, and clotting factors. The report also provides some advice on generation of normal reference ranges, as well as solutions for troubleshooting prolonged APTTs, when performing factor testing or searching for inhibitors.
Keywords: activated partial thromboplastin time; factor sensitivity; heparin sensitivity; lupus anticoagulant sensitivity